On the uptake of flexible working arrangements and the association with human resource and organisational performance outcomes - Berkery, Elaine; Morley, Michael J.; Tiernan, Siobhan; Purtill, Helen; Parry, Emma (Wiley, 2017)
The aim of this study was to identify bundles of flexible working arrangements (FWAs) from data provided by 1,064 organizations in seven EU countries, and to relate bundle membership to demographic variables and human resource (HR) and organizational performance outcomes. Using Ward's hierarchical clustering algorithm we identified four distinct bundles of FWAs based on the uptake of twelve individual FWAs across the sample of organizations. Bundle 1 represents organizations engaging in a high level of annual hours contracts; bundle 2 represents more traditional work practices; bundle 3 represents organizations mainly offering shift-work and bundle 4 represents organizations with a high uptake of flexi-time. The demographic profile of organizations recorded across each of the four bundles was significantly different. Finally, significant associations were found between the bundle membership and employee turnover (p < 0.001), absenteeism (p < 0.001) and productivity (p < 0.015). The implications of these results are discussed and directions for future research are proposed.
Keywords: performance; HRM; employment contract; productivity; flexible work arrangements; absenteeism; employee turnover; CRANET